2021
DOI: 10.4236/ajps.2021.121008
|View full text |Cite
|
Sign up to set email alerts
|

Tree Species Composition and Diversity in the Riparian Forest of Lake Barombi Kotto, Cameroon

Abstract: Tree species composition and diversity were investigated in the riparian forest around Lake Barombi Kotto, Cameroon. This study aimed at determining the tree species composition, population structure, and providing evidence of anthropogenic disturbances in the riparian forest of Lake Barombi Kotto. The objectives were to determine the tree species composition and diversity in the riparian forest around Lake Barombi Kotto, to elucidate the forest structure and to document the anthropogenic disturbances in this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
2
1
Order By: Relevance
“…The total basal area values recorded in this study were higher than those reported in some sacred riparian (gallery) forests in Africa e.g. 0.01-0.91 m 2 ha −1 as shown by Fariyah et al (2020) andMiranda Egbe et al (2021). Factors like the regeneration potentials of dominant woody species with weak regression slopes in the study sites , microsite conditions, water flow effect and species biology (Naiman et al 2008) have been reported to be responsible for variations in these observations.…”
Section: Discussioncontrasting
confidence: 56%
“…The total basal area values recorded in this study were higher than those reported in some sacred riparian (gallery) forests in Africa e.g. 0.01-0.91 m 2 ha −1 as shown by Fariyah et al (2020) andMiranda Egbe et al (2021). Factors like the regeneration potentials of dominant woody species with weak regression slopes in the study sites , microsite conditions, water flow effect and species biology (Naiman et al 2008) have been reported to be responsible for variations in these observations.…”
Section: Discussioncontrasting
confidence: 56%
“…Tree and shrub species which were common in both study areas were from the Fabaceae, Malvaceae Open Journal of Ecology and Euphorbiacea families. Fabaceae has been found to be the most species rich family in most forest formations [34]. The species richness of these families identified in the study areas can be attributed to their good seed dispersal mechanisms which make them to be capable of colonizing different forest fragments, coupled with their ability to produce numerous seeds which eventually establish at suitable sites.…”
Section: Riparian Vegetation Composition and Structure Across Land Usementioning
confidence: 87%
“…al., 2019;Michez et al, 2017). According to floristic studies, riparian forests present heterogeneity in the dynamics, composition and structure of species (Miranda et. al., 2021).…”
Section: Introductionmentioning
confidence: 99%